PENGARUH PROFITABILITAS, LIKUIDITAS DAN SOLVABILITAS TERHADAP NILAI ENTITAS DENGAN UKURAN ENTITAS SEBAGAI VARIABEL MODERASI - Adelina, Friska; Jaya R, Tresno Eka; Sasmi, Aji Ahmadi (LPPM Universitas Bina Bangsa, 2023)
The purpose of this research is to examine the effect of profitability, liquidity, solvency on entity value with entity size as a moderating variable. The population in this study are entities listed in the LQ45 index for 2022. The number of samples in this study were 35 entities. The sampling technique used purposive sampling method. The research method used is quantitative with secondary data. Methods of data analysis using multiple linear regression analysis and moderation linear analysis with SPSS 25. The results of this study provide empirical evidence that partially the profitability and solvency variables have a significant effect on firm value, while the liquidity variable has no effect on firm value